Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT Astron Optindo Industries - Bambang Nuryatin (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
Human resources is the most important element to achieve the company goals. The performance of company can be influenced with several things such as motivation, satisfaction, and disciplie. It wiil be give the company good impact. Because of their performance. This study aims to determine whether there is an influence of work motivation and work discipline on employee performance with job satisfaction as an intervening variable at PT Astron Optindo Industries. The research using quantitave description menthod with structural equation model analysis (SEM). The data used in this study uses primary data obtained from the answers of 100 respondents.The results show that motivation has a positive influence on employee job statisfaction, shown with a p value are 0,001. Discipline has a positive influence on employee job satisfaction, shown with a p value are 0,000. Motivation has has a positive influence on employee job satisfaction, shown with a p value are 0,000. Discipline has a positive influence on employee performance with a p value of 0,000. Satisfaction has has a positive influence on employee job satisfaction, shown with a p value are 0,000. Satisfaction has has a positive influence on employee job satisfaction, shown with a p value are 0,006. Satisfaction has a positive influence on employees as mediators of motivation and discipline on employee performance.